Divergent Synthesis of Chiral Covalent Organic Frameworks - Wang, Li‐Ke; Zhou, Jing‐Jing; Lan, Yu‐Bao; Ding, San‐Yuan; Yu, Wei; Wang, Wei (Angewandte Chemie International Edition, 2019)
Featuring the simultaneous generation of a library of compounds from a certain intermediate, divergent synthesis has found increasing applications in the construction of natural products and potential medicines. Inspired by this approach, presented herein is a general strategy to introduce functionality, in a divergent manner, into covalent organic frameworks (COFs). This modular protocol includes two stages of covalent assembly, through which functional COFs can be constructed by a three‐step transformation of a key platform molecule, such as 4,7‐dibromo‐2‐chloro‐1H‐benzo[d]imidazole (DBCBI). Constructed herein are four types of chiral COFs (CCOFs) from DBCBI by nucleophilic substitution, Suzuki coupling, and imine formation. The unique array of eight isoframework CCOFs allowed investigation of their catalytic performance and structure–activity relationship in an asymmetric amination reaction. COF it up: A divergent strategy has been used to construct a combinatorial library of functional covalent organic frameworks (COFs) from a platform molecule. An array of eight isoframework chiral COFs allowed investigation of their catalytic performance and structure–activity relationship in an asymmetric amination reaction.